2022
DOI: 10.1021/acs.orglett.2c03648
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4-Imidazolidinones from Diamides and Ethynyl Benziodoxolones via Double Michael-Type Addition: Ethynyl Benziodoxolones as Electrophilic Ynol Synthons

Abstract: The moiety of 4-imidazolidinone is an important structural motif in organic synthesis and medicinal chemistry. We present the synthesis of 4-imidazolidinones from various diamides with ethynyl benziodoxolones through double Michael-type addition, which is an unprecedented reaction mode for hypervalent alkynyl iodine compounds. cis-2,5-Disubstituted 4-imidazolidinones were diastereoselectively synthesized from amino acid derived diamides. Having derivatized the 4-imidazolidinones, several control experiments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…459,[484][485][486][487][488][489][490][491][492][493][494][495][496] Besides, several metal-free alkynylation reactions have also been reported for the synthesis of numerous synthetically important targets, including heterocycles. [497][498][499][500][501][502][503][504][505][506][507] Representative examples for metal-catalyzed, photoredox and metal-free alkynylation reactions using EBXs are presented in Scheme 43.…”
Section: Hypervalent Heterocyclic Compounds Of Iodine(iii)mentioning
confidence: 99%
“…459,[484][485][486][487][488][489][490][491][492][493][494][495][496] Besides, several metal-free alkynylation reactions have also been reported for the synthesis of numerous synthetically important targets, including heterocycles. [497][498][499][500][501][502][503][504][505][506][507] Representative examples for metal-catalyzed, photoredox and metal-free alkynylation reactions using EBXs are presented in Scheme 43.…”
Section: Hypervalent Heterocyclic Compounds Of Iodine(iii)mentioning
confidence: 99%
“…Following derivatization of the 4-imidazolidinones, we con-ducted several control experiments and density functional theory calculations to gain mechanistic insight. [41] Solid-Phase Synthesis: Solid-phase synthesis techniques offer practical advantages for the synthesis of imidazolidine derivatives, particularly in the context of combinatorial chemistry. Immobilizing the growing compound on a solid support allows for efficient purification and screening of diverse compounds, expediting the optimization process.…”
Section: Other Synthesis Approaches Used For Accessing Imidazolidinon...mentioning
confidence: 99%
“…The diastereoselective synthesis of cis‐2,5‐disubstituted 4‐imidazolidinones was achieved using amino acid‐derived diamides. Following derivatization of the 4‐imidazolidinones, we conducted several control experiments and density functional theory calculations to gain mechanistic insight [41] …”
Section: Other Synthesis Approaches Used For Accessing Imidazolidinon...mentioning
confidence: 99%
“…A wide range of heterocycles can be synthesized using EBXs under transition metalfree conditions [70,[145][146][147]. Cossy et al reported the synthesis of tetrahydropyrazines 134 from diamides 133 using TMS-EBX 51c in the presence of a strong base through 6-endo-dig cyclization of the ynamide intermediate A (Scheme 28a) [70].…”
Section: Transition Metal-free Reactionsmentioning
confidence: 99%